Transradial approach for acute stroke intervention: technical procedure and clinical outcomes. Issue 1 (27th November 2019) - Khanna, Omaditya; Mouchtouris, Nikolaos; Sweid, Ahmad; Chalouhi, Nohra; Ghosh, Ritam; Al Saiegh, Fadi; Gooch, Michael R; Tjoumakaris, Stavropoula; Rosenwasser, Robert H; Romo, Victor; Jabbour, Pascal
Abstract : Background and purpose: Radial artery catheterisation is an alternate route of access that has recently started to gain more widespread use for neuroendovascular procedures, including acute stroke intervention. In this small case series, we present our institution's outcomes in patients undergoing acute stroke interventions via transradial access. Materials and methods: We present a retrospective study of 15 patients who underwent acute stroke intervention via radial artery access. We analyse these patients' periprocedural and clinical outcomes after undergoing mechanical thrombectomy. Results: A total of 15 consecutive patients were included in the study (9 males and 6 females), and all patients were able to successfully undergo mechanical thrombectomy via radial artery access. The mean time of arterial puncture to reperfusion was 50±28 min (range: 15–104). A TICI 2b/3 revascularisation was achieved in 13/15 patients (87%); a TICI 1 and TICI 2a outcome was achieved on the other two patients. One patient incurred an iatrogenic vessel dissection during the procedure. Eight of out 15 patients (53%) had favourable mRS (0–3) at the time of discharge from the hospital. Conclusion: Radial artery catheterisation is technically feasible for performing acute stroke interventions with favourable time to revascularisation and good overall clinical outcomes.